Exploiting amyloid: how and why bacteria use cross-β fibrils. (20th July 2012) - Sawyer, Elizabeth B.; Claessen, Dennis; Gras, Sally L.; Perrett, Sarah
Abstract : Many bacteria produce protein fibrils that are structurally analogous to those associated with protein misfolding diseases such as Alzheimer's disease. However, unlike fibrils associated with disease, bacterial amyloids have beneficial functions including conferring stability to biofilms, regulating development or imparting virulence. In the present review, we consider what makes amyloid fibrils so suitable for these roles and discuss recent developments in the study of bacterial amyloids, in particular the chaplins from Streptomyces coelicolor . We also consider the broader impact of the study of bacterial amyloids on our understanding of infection and disease and on developments in nanotechnology.